Mobile search assistance from HCI aspect. (17th March 2011) - Arase, Yuki; Hara, Takahiro; Komaki, Daijiro; Nishio, Shojiro
Mobile internet access has become an important technology to our life. According to this trend, search engines have been providing search services for mobile phones. Since a mobile phone has a limited interface, such as a small screen and keypad, even simple interactions are burdensome for users. Therefore, to provide comfortable web browsing experience, efforts on HCI aspect are also essential. In this paper, we describe our studies that tackle this problem by HCI-based approach. We propose systems that reduce the number of operations on inputting a query to a search engine, enable clipping and saving a web content, and assist cooperative web search conducted by multiple mobile users.